2004
DOI: 10.1051/0004-6361:20047188
|View full text |Cite
|
Sign up to set email alerts
|

Collisional depolarization and transfer rates of spectral lines by atomic hydrogen

Abstract: Abstract. The semi-classical theory of collisional depolarization of spectral lines that we have applied to neutral atoms in previous papers is extended to spectral lines of singly ionised atoms. In order to validate our general theory, we compare our results to quantum chemistry calculations obtained for the particular cases of the 3d 2 D and 4p 2 P states of the CaII ion. As a demonstration of the universality of our theory and the easiness of its application, we calculate depolarization and polarization tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…A semi-classical theory underlying the calculation of the depolarization and polarization transfer rates by isotropic collisions of ions with neutral hydrogen is detailed and validated in Derouich et al (2004). They found that the percentage of error on the semi-classical rates with respect to the available quantum chemistry rates is 4% to 7% (see Sect.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…A semi-classical theory underlying the calculation of the depolarization and polarization transfer rates by isotropic collisions of ions with neutral hydrogen is detailed and validated in Derouich et al (2004). They found that the percentage of error on the semi-classical rates with respect to the available quantum chemistry rates is 4% to 7% (see Sect.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…By comparing to the reference value of C 0 ( 3 2 → 5 2 )(T = 5000K)) given in Equation 17 of Derouich et al (2004), we found that re(Ca II) ≃ 2 %, re(Ba II) ≃ 19 %, re(Sr II) ≃ 4 %. Note that in Derouich et al (2004), the polarization transfer rates are denoted by…”
Section: Polarization Transfer Rates Between the Levelsmentioning
confidence: 68%
“…After that the code of collisions should be run to get the collisional rates level by level. This is a strong restriction which hinders the generalization of the DSB results published in Derouich et al (2004). That restriction has been removed for the p-states of ions in the recent paper of Derouich (2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Rough estimates for the depolarizing rates can be obtained from a dipole-dipole van der Waals approximation for the atom-H • (Lamb & ter Haar 1971, see also Landi Degl'Innocenti & Landolfi 2004. More recently, Derouich et al (2003aDerouich et al ( , 2003bDerouich et al ( , 2004aDerouich et al ( , 2004bDerouich et al ( , 2005; Derouich & Barklem (2007) used ab initio interaction potentials and a semi-classical approach using straight line trajectories at different impact parameters. Kerkeni et al (2000); Kerkeni (2002); Kerkeni & Bommier (2002); Kerkeni et al (2003) have calculated depolarizing rates with neutral hydrogen with a fully quantum mechanical approach for the Hamiltonian interaction and dynamics.…”
Section: Introductionmentioning
confidence: 99%